APLIKASI KNO, TERHADAP PERTUMBUHAN DAN BASIL TANAMAN KAILAN (BRASSKA ALBOGLABRA L.) - Elzazuhry ' (Universitas Riau, 2010)
Kailan (Bnusiea aiboglabra L) is horticultural crop as food substance required by human iieingwith high economic value. This research was carried out using Complete Randomized Design with sixtreatments and three replications. Treatments were: without application of KJVO^ (control), application of 0.5g/polybag KNO, and 1 g/potybag KNO, to die soO, 2 g«1,4 g/l, and « g1 KNO^ sohition applied to the leaves. Ilie/result of the research showed tliat the applicatktn of KNO, significantly affected the crop age, fresh weq(ht ofthe crop and consummable weight. The best treatment was application of KNO, solution to the leaves withconcentration of 4 g/L.